Mechanisms of plant cell wall surveillance in response to pathogens, cell wall-derived ligands and the effect of expansins to infection resistance or susceptibility - Narváez-Barragán, Delia A.; Tovar-Herrera, Omar E.; Guevara-García, Arturo; Serrano, Mario; Martinez-Anaya, Claudia (Frontiers in Plant Science, 2022)
Cell wall integrity is tightly regulated and maintained given that unintended or uncontrolled modification of cell walls could render plants vulnerable to biotic and/or abiotic stresses. Expansins are plant cell wall-modifying proteins active during many developmental and physiological processes, but they can also be encoded by bacteria and fungi during interaction with plant hosts. Cell wall alteration brought about by ectopic expression, overexpression, or exogenous addition of expansins from either eukaryote or prokaryote origin can in some instances provide resistance to pathogens, while in other cases plants become more susceptible to infection. In these circumstances altered cell wall mechanical properties might be directly responsible for pathogen resistance or susceptibility outcomes. Simultaneously, through membrane receptors for enzymatically released cell wall fragments or by sensing modified cell wall barrier properties, plants trigger intracellular signaling cascades inducing defense responses and reinforcement of the cell wall, contributing to various infection phenotypes, in which expansins might also be involved. Here, we review the plant immune response activated by cell wall surveillance mechanisms, cell wall fragments identified as responsible for immune responses, and expansin’s roles in resistance and susceptibility of plants to pathogen attack.